Prevalência de Diabetes e de fatores de risco e proteção para saúde em indivíduos com e sem Diabetes no Brasil (20062014) - Ana Paula Della Nina de Oliveira (2016)
Introduction: Diabetes mellitus is the most common chronic diseases in much of the world, with an increasing prevalence in developed and in developing countries. Among individuals with diabetes, adherence to good health behaviors is recognized for providing better quality of life and more favorable prognosis. Objective: This study aims to identify the prevalence of diabetes and conducting risk behaviors and protection for the health of adults with diabetes in Brazil's 26 state capitals and the Federal District in the period 2006-2014. Methods: We analyzed data from 465,053 subjects interviewed by VIGITEL (Surveillance System for Risk and Protective Factors for Chronic Diseases) between 2006 and 2014. Since 2006 VIGITEL annually interview a random sample of individuals 18 years living in Brazilian state capitals and the Federal District (about 2 thousand people in each site), consolidating its position as the main source of information on the topic in the country. Regression models were used to investigate significant variations in the prevalence of diabetes and adherence to health behaviors among individuals with and without diabetes. Results: The prevalence of diabetes has increased significantly in the studied population, from 5.5% to 8.0% between 2006 and 2014 (0.26 percentage points (pp)/year). Individuals with diabetes had a lower frequency of risk behaviors and increased frequency of protective behaviors compared to individuals without diabetes. The largest differences were observed in the case of consumption of softdrinks and sweetened beverages (9.5% vs. 25.0%), alcoholic beverages (8.7% vs. 17.7%) and whole fat milk (44.7% vs. 55.8%), while the lowest were checked for regular consumption of fruits and vegetables (40.8% vs. 33.4%) and meat with fat (24.0% vs 32.2%). However, both groups also showed high frequency of negative behaviors such as drinking whole fat milk or sodas and sugary drinks and insufficient physical activity. Conclusion: The prevalence of diabetes increased significantly inBrazil between 2006 and 2014. Although individuals with diabetes compared to individuals without diabetes, show a higher frequency of protective behaviors and those lower risk, the current situation still demand greater effectiveness both in prevention of diabetes in individuals without the disease and in its management in already sick individuals.